STRATEGI DAN PRIORITAS PENCEGAHAN SERTA PENGENDALIAN IUU FISHING DI PPP BANDA - Tomasila, Leopold A; Sahilatua, Jozef M; Tupamahu, Agustinus; Tuhumena, Lolita (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Background: The issue of IUU fishing is a major threat to fish stocks in today's world, regionally and nationally. In order to prevent and control IUU fishing, supervision at fishing ports needs attention to be evaluated. Methods: This study was conducted for 5 months from August to December 2018. The data analysis used was SWOT and AHP. Results:The results obtained in this study were optimization of ASN capacity development for IUUF prevention and control (0.0257), increased education and outreach for fishermen about the importance of IUUF prevention and control (0.0195), RPP policy (local fisheries management plan) (0.0180), Increased accessibility of fishermen and fisheries officers (0.0134), Improved TPI functions (0.0089), Improved coordination between fishermen, entrepreneurs and fisheries supervisors (0.0086), Improved monitoring, controlling and surveillance (MCS ) between ASN and the community (0.0058). Conclusion: There has been an increase in strategies and priorities for prevention and control of iuu fishing in PPP Banda.